Decision Support System for Forecasting Palm Fruit Production With Trend Moment Methode Case Study of Kasus PT. Plantation Archipelago III (Persero) North Aek Nabara - Siregar, Eka Maya Putri; Dalimunthe, Abdul Hakim; Samsir, Samsir; Siagian, Taufiqqurrahman (Journal of Computer Science and Information System(JCoInS), 2023)
This study aims to determine the application of the Itrend moment method in determining forecasting of palm fruit production. Oil palm plantations are one of the industrial strategies in Indonesia. Oil palm trees are plants that provide many important roles for humans, such as raw materials that can be used as fuel and produce food oil. Therefore, it is not surprising why there are so many oil palm plantations scattered throughout the archipelago. One of them at Pt. Perkebunan Nusantara III (Persero) Kebun Aek Nabara Utara where the company is engaged in oil palm and rubber plantations. This research is supported by using the trend moment method to facilitate forecasting of palm fruit production. By doing forecasting, it will be easier to find out the amount of palm fruit production just by forecasting some symptoms, such as weather, climate, and temperature. In addition, this method is assisted by using a system, namely a decision support system. Where able to take or determine decisions from a forecasting (forecasting).